Combining different treatment philosophies and techniques to reach the desired treatment goal using butterfly system-customizing orthodontic treatment - Lekhadia, Dhaval (Journal of Oral and Dental Sciences, 2017)
This case report describes the orthodontic treatment of an 18-year-old male patient who presented with Straight profile; tongue thrust habit, proclined upper incisors, generalised spacing in upper and lower arches, Katz's class II premolar relation unilaterally, class II canine relation unilaterally with increased overjet and overbite. A butterfly system was used in the treatment combined with frictionless biomechanics in the initial stage of treatment followed by continuous arch mechanics in the later part of treatment. A tongued crib was used to stop the tongue thrust habit along with one elastic swallow exercise. Micro-implant anchorage was used unilaterally in the upper arch for retraction of the entire segment and correction of the unilateral class II canine and premolar relationship. To avoid a dished in profile, a non-extraction treatment was executed. Final corrections of distally tipped canines were achieved using conventional Beggâ€™s Â uprighting auxiliaries in the vertical slots of butterfly system in the finishing stage. The case was finished using bite settling elastics. Total treatment time was 1 year 2 months. Aesthetic and functional goals were achieved satisfactorily with proper selection of biomechanics.
Keywords: Sectional Mechanics; Butterfly system; Micro-implant; Tongue crib; vertical slots